A review of the future impact of climate change in Chile: economic output and other outcomes - Madeira, Carlos (Mitigation and adaptation strategies for global change, 2022)
I review several studies for the future impact of climate change during the twenty-first century, making a comprehensive summary of the effects estimated for Chile. Several studies suggest that Chile is likely to suffer mild effects in terms of GDP growth, labor productivity, and mortality costs from climate change in the twenty-first century. However, there is substantial uncertainty around these estimates, with at least one study predicting significant GDP losses due to adaptation difficulties. I compute a principal component factor that summarizes the information from six different measures of GDP loss as a single variable, showing a low principal component value for Chile. Furthermore, several studies find that Chile may face non-GDP-related problems from climate change, such as air pollution, fire hazards, drought, water stress, biodiversity loss, ecosystem damages, and human migration. Finally, according to several indexes, Chile is still only in the middle of the table in terms of policy, infrastructure, and climate readiness. Chile is also below several developed countries in terms of government expenditure on environmental protection and environmental taxes, while at the same time presenting a high value of fossil fuel subsidies. Therefore, there is substantial room to improve economic and environmental policies to fight climate change.